Release of Cytochrome c, Bax Migration, Bid Cleavage, and Activation of Caspases 2, 3, 6, 7, 8, and 9 during Endothelial Cell Apoptosis - Granville, David J. (American Society for Investigative Pathology, 1999)
Although the executioner phase of apoptosis has been well defined in many cell types, the subcellular events leading to apoptosis in endothelial cells remain undefined. In the current study, apoptosis was induced in primary human umbilical venous endothelial cells by the photosensitizer verteporfin and light. Release of mitochondrial cytochrome c into the cytosol was detectable immediately and accumulated over 2 hours after treatment while cytosolic levels of the proapoptotic Bcl-2 family member, Bax, decreased reciprocally over the same time period. Cleavage of another proapoptotic Bcl-2 family member, Bid, was observed by 2 hours after treatment. Although Bid cleavage has been shown to occur as an upstream event responsible for inducing cytochrome c release, we demonstrate that Bid cleavage can also occur after cytochrome c release. Activation of caspases 2, 3, 6, 7, 8, and 9 occurred following the release of cytochrome c, and cleavage of downstream substrates was observed. In summary, endothelial cell death involves the cellular redistribution of Bax and cytochrome c, followed by the activation of multiple caspases which manifest the apoptotic phenotype.